Mathematical modeling and DLQR based controller design for a non-minimum phase Electro Hydraulic Servo system (EHS) - Ahmed, Mazid Ishtique; Azad, Akm M.M.Abdul Malek (© 2016 IEEE, 2018)
This conference paper was published in the IEEE Region 10 Conference, TENCON 2016; Marina Bay SandsSingapore; Singapore; 22 November 2016 through 25 November 2016 [© 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/TENCON.2016.7848339 The Journal's website is at: https://ieeexplore.ieee.org/document/7848339/